Development of conflict management strategies to increase the organizational effectiveness in Nordic companies - Violetta Bankovskaya 1988- (2012)
The thesis explores the nature of conflict, the conflict process, conflict resolution skills and conflict management techniques in the case of Icelandic companies. The most important values that determine the work in Icelandic organizations are: egalitarianism, which includes power distance, individualism, femininity and unrealistic optimism, the “action-poet” psyche and the “fisherman mentality”. Because of unique mentality and very unusual organization culture of Icelandic people it attracted the author to explore how conflict management practice works in Iceland and what managers can improve in their conflict resolution approach to increase the productivity of the organization. The theoretical chapter gives an overview of sources and types of conflict, conflict resolution skills and conflict management techniques. Exploring in-depth the literature review is the main theoretical base for the analysis. Findings of this research include that Icelandic employers are quite familiar with conflict resolution process and the managers use in practice many of the conflict resolution techniques. But still they have complaints about conflicts from the employees. The main types of conflict in Icelandic organizations are Interpersonal and Intragroup conflicts. According to the conflict resolution model based on the literature review Icelandic organizations have some gaps in their approach of conflict resolution. The findings of the research inform the managers how to improve their conflict resolution approach and accordingly to increase the productivity of the whole organization. Keywords: conflict management, conflict resolution skills, conflict resolution styles, conflict resolution techniques, conflict resolution model